Kedudukan Fraksi di Dewan Perwakilan Rakyat Daerah Sumatera Utara - Endang Ekowati; Amanda Fadilsyah Giofani; Muhammad Rahma Doni; Amirul Triasdana; Maulana Ibrahim (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
The Regional People's Representative Council is a people's representative institution in the regional area and has the position of being an organizing element in regional government in provinces and districts/cities in Indonesia. DPRD has the task and authority as the party that carries out the formation of regional regulations in collaboration with the local regional head, as well as overseeing the implementation of regional regulations and the management of the APBD. DPRD members are required to join one of the factions, which has the task of coordinating member activities and maximizing the performance of DPRD members. The faction also has the responsibility to provide an evaluation of the performance of members and provide reports regarding the results of the evaluation to the public. Keywords :Faction, Regional People's Representative Council, North Sumatra